Promoting skill transfer for human capacity development in Papua New Guinea. (Metro Manila, Philippines Asian Development Bank, 2017)
Pacific countries lack workers with construction skills and rely on large firms to import skilled workers for large infrastructure projects.
Keywords: Vocational education -- Papua New Guinea; Technical education -- Economic aspects; Electronic books